Financial Charges Within Budget Impact Investment Fund School Educational Services San Augustine IED (2014)
The District Educational Institution San Agustín of the town 18 Rafael Uribe Uribe, located in the city of Bogotá, has annually with a budget that is intended for educational activities, among which are: Sexual Education, Training Exchange, Technical Training for labor, environment and disaster prevention, purchase of equipment for the benefit of students, Promotion of culture, other projects, the idea of these projects is to strengthen the PEI (Institutional Education Project) school, among others. However, no yearly analyzes and studies of effectiveness and compliance with the objectives of these programs are made, nor is has a detailed analysis of the workings that are given to these resources, stipulating both audit and financial control and to management of such activities.Because of this problem, the need for a study of the investment costs within the budget of the College to determine if indeed the economic, technological and human resources are meeting the work and functions required for this purpose, or arises if on the contrary there are potholes and inefficiencies in these aspects.